Analyzing ECoG Distortions in Cochlear Implant Patients and Gerbils. (23rd August 2013) - Forgues, Mathieu; Adunka, Oliver F.; Choudhury, Baishakhi; Campbell, Adam P.; Buchman, Craig A.; Fitzpatrick, Douglas
Abstract : Objectives: 1) Describe how rectification and saturation in hair cell and neural responses contribute to electrocorticography (ECoG) recordings in an animal model. 2) Analyze distortions in intraoperative recordings of cochlear implant patients. Methods: ECoG potentials from the round window (RW) of humans and gerbils were measured to tones of different frequencies and intensities. Human subjects receiving cochlear implants had a variable degree of hearing loss. The gerbils had normal hearing or a pattern of high frequency, noise‐induced hearing loss similar to many cochlear implant recipients. In our animal model, forward masking, simultaneous masking, and application of a neurotoxin to the RW were used to isolate hair cell and neural responses. Results: In both humans and gerbils, discrete patterns of distortions in the ECoG waveform were present that had either a hair cell or neural origin. Distortions due to phase locking of nerve fibers (the ANN) were the main cause of distortion at low frequencies and up to moderate intensities, while distortions seen at high intensities across all frequencies suggested saturation of stereociliary movement in the CM. Conclusions: Distortions originating from phase locking in nerve fibers can be diminished with forward masking or a neurotoxin, helping to isolate the relative contribution of nerve fibers and hair cells. Distortions in the animal model are also present in ECoG recordings in cochlear implant patients, and can have hair cell or neural origins.